Multiple pulmonary embolisms in a male marathon athlete: Is intense endurance exercise a real thrombogenic risk? - Sanz de la Garza, M.; Lopez, A.; Sitges, M. (Scandinavian Journal of Medicine & Science in Sports, 2017)
Intense endurance exercise could be associated with multiple thrombogenic risk factors, including dehydration, hemoconcentration, inflammation, and injuries. Despite an increasing number of reported cases of deep venous thrombosis (DVT) in athletes that is raising awareness in the medical community, the prevalence is not well established and evidenced-based guidelines for management of this clinical scenario are lacking. We present an episode of unprovoked DVT and multiple pulmonary embolisms with severe right ventricular dysfunction in a male runner. We highlight the challenge of diagnosing DVT and pulmonary embolism in athletes due to frequently atypical symptomatology and the emergent need for longitudinal studies to evaluate their thrombogenic risk and develop specific guidelines in this field.